Oocyte Cryostorage to Preserve Fertility in Oncological Patients - Alberto Revelli; Emanuela Molinari; Francesca Salvagno; Luisa Delle Piane; Elisabetta Dolfin; Simona Ochetti (Obstetrics and Gynecology International)
Thanks to the progress in oncostatic treatments, young women affected by cancer have a fairly good chance of surviving the disease and leading a normal post-cancer life. Quite often, however, polychemiotherapy and/or radiotherapy can induce ovarian damage and significantly reduce the content of follicles and oocytes inside the ovary, thus predisposing the patient to menstrual disorders, infertility, and precocious menopause. Several techniques have been proposed to preserve fertility in these patients; among them oocyte collection and cryopreservation prior to the oncostatic treatment has been widely applied in the last decade. The proper indications, the permitting conditions, the available hormonal stimulation protocols, as well as the effectiveness and limits of this option will be discussed herein, with a comprehensive and up-to-date review of the two techniques commonly used to cryostore oocytes, the slow-freezing technique and the vitrification technique.